Leadership and management in the undergraduate medical curriculum: a qualitative study of students' attitudes and opinions at one UK medical school. Issue 6 (25th June 2014) - Quince, Thelma; Abbas, Mark; Murugesu, Sughashini; Crawley, Francesca; Hyde, Sarah; Wood, Diana; Benson, John
Abstract : Objective: To explore undergraduate medical students' attitudes towards and opinions about leadership and management education. Design: Between 2009 and 2012 we conducted a qualitative study comprising five focus group discussions, each devoted to one of the five domains in the Medical Leadership Competency Framework, (Personal Qualities, Working with Others, Managing Services, Improving Services and Setting Direction). Each discussion examined what should be learnt, when should learning occur, what methods should be used, how should learning be assessed, what are the barriers to such education. Participants: 28 students from all three clinical years (4–6) of whom 10 were women. Results: 2 inter-related themes emerged: understanding the broad perspective of patients and other stakeholders involved in healthcare provision and the need to make leadership and management education relevant in the clinical context. Topics suggested by students included structure of the National Health Service (NHS), team working skills, decision-making and negotiating skills. Patient safety was seen as particularly important. Students preferred experiential learning, with placements seen as providing teaching opportunities. Structured observation, reflection, critical appraisal and analysis of mistakes at all levels were mentioned as existing opportunities for integrating leadership and management education. Students' views about assessment and timing of such education were mixed. Student feedback figured prominently as a method of delivery and a means of assessment, while attitudes of medical professionals, students and of society in general were seen as barriers. Conclusions: Medical students may be more open to leadership and management education than thought hitherto. These findings offer insights into how students view possible developments in leadership and management education and stress the importance of developing broad perspectives and clinical relevance in this context.